A study of pulsed thermography for life assessment of thin EB-PVD TBCs undergoing oxidation ageing. (December 2017) - Tinsley, Lawrence; Chalk, Christine; Nicholls, John; Mehnen, Jörn; Roy, Rajkumar
Abstract: This paper presents an assessment of ageing for thin Thermal Barrier Coatings (TBC) using active thermography. As TBCs undergo ageing during their service life, sintering changes the porosity, elements migrate from the substrate, and micro-cracks build up in the structure of the material, exhibiting a change in thermal conductivity and diffusion properties. As the material ages and these properties change over time, it is possible to exploit trends in this change for characterisation of coating ageing, which would provide a diagnostics tool to estimate remaining useful life. In this study, through-depth diffusivity measurement has been applied to thin EB-PVD coatings which are artificially aged via oxidation furnace cycles. In order to address the difficulties of capturing a fast thermal event in a thin coating, a novel parametric study approach has been carried out to optimise data capture and analysis, maximising available frames for the model fitting step. Through-depth diffusivities have been measured during ageing for six samples, yielding a repeatable trend in thermal diffusivity measurements, with three features, which can be exploited for ageing characterisation of thin EB-PVD TBCs, and used as an alarm of imminent failure. Highlights: A pulsed thermographic inspection of thin thermal barrier coatings was performed during oxidation to predict remaining life. A parametric study is conducted to opimise data capture parameters for a fast thermal event. The measured thermal diffusivity values displayed three trend features useful for ageing assessment and warning of failure.